Ceria Boosting on In Situ Nitrogen-Doped Graphene Oxide for Efficient Bifunctional ORR/OER Activity - Kashinath, L.; Byrappa, K. (Frontiers in Chemistry, 2022)
In the present work, a highly efficient and excellent electrocatalyst material for bifunctional oxygen reduction/evolution reaction (ORR/OER) was synthesised using microwave-assisted hydrothermal method. In brief, ultrafine hexagonal cerium oxide (CeO2) nanoparticles were tailored on the layered surface of in-situ nitrogen doped graphene oxide (NGO) sheets. The nanocomposites exhibited a high anodic onset potential of 0.925 V vs RHE for ORR activity and 1.2 V for OER activity with a very high current density in 0.5 M KOH. Influence of oxygen cluster on Ce3+/Ce+4 ions decoration on out/inward of in-situ nitrogen coupled GO enhanced the physicochemical properties of composites and in turn increased electron transferability. Microwave assisted hydrothermal coupling technique provides a higher density, active sites on CeO@NGO composites and oxygen deficiency structures in ultrafine Ce-O particles boosts in higher charge transferability in the composites. It is believed that the physical states of Ce-N-C, Ce-C=O, and higher amount of oxygen participation with ceria increase the density of composites that in turn increases the efficiency. N-doped graphene oxide promotes high current conduction and rapid electron transferability while reducing the external transport resistance in oxygen electrocatalysis by sufficient mass transfer through in-built channels. This study may provide insight knowledge of Ce-enabled bifunctional activity to guide for the design of a robust catalyst for electrochemical performance.